General genetic and acquired risk factors, and prevalence of peri‐implant diseases – Consensus report of working group 1. (3rd September 2019) - Meyle, Joerg; Casado, Priscila; Fourmousis, Ioannis; Kumar, Purnima; Quirynen, Marc; Salvi, Giovanni E.
Abstract: For decades, oral implants have been used successfully for the replacement of missing teeth. Nevertheless, peri‐implant diseases have become an increasingly important issue in daily practice. In this working group, the prevalence of peri‐implant mucositis and peri‐implantitis, as well as different general risk factors and their impact on the onset and progression of peri‐implant diseases, were discussed based on reviews reflecting the current state of evidence. The influence of smoking on the peri‐implant bone‐healing process and its association with peri‐implantitis has been explored in the current literature, demonstrating that smoking is an important risk indicator for the development of peri‐implantitis and implant loss. Compared with non‐smokers, smokers have a higher potential for pathological peri‐implant bone loss, which is also influenced by poor oral hygiene. Despite the fact that a growing number of genetic polymorphisms have been identified and related to periodontal diseases, there are still no genetic patterns that could act as adjuncts to clinical diagnostics in order to identify patients at higher risk of peri‐implant diseases. Long‐term medications, such as bisphosphonate therapy (> 3 years), may have an impact on implant loss. A higher incidence of implant failure was reported in patients using selective serotonin reuptake inhibitors in anti‐depression therapy. Alcoholism (defined as more than 5 units a day) has been associated with implant loss in retrospective and case–control studies, as well as in animal studies.